Tijuana dreaming : life and art at the global border - Kun, Josh; Montezemolo, Fiamma (Duke University Press, 2012)
Tijuana Dreaming is an unprecedented introduction to the arts, culture, politics, and economics of contemporary Tijuana, featuring selections by prominent scholars, journalists, bloggers, novelists, poets, curators, and photographers from Tijuana and greater Mexico.